CONFOCAL MICROSCOPY STUDY OF BIOLOGICAL PECULIARITIES OF SCAFFOLD MADE FROM RECOMBINANT SPIDER SILK - O. L. Pustovalova; I. I. Agapov; M. M. Moisenovich; P. S. Eremin; A. A. Kazulina; A. Y. Arhipova; A. A. Ramonova; V. G. Bogush; V. I. Sevastianov; M. P. Kirpichnikov (Вестник трансплантологии и искусственных органов, 2009)
We studied the viability and dynamic of cell distribution during long-term cultivation of broblasts 3T3 in spider silk spidroin 1-based scaffold. Laser scanning confocal microscopy is shown to have advantages for visualization of cells situated on the external and internal surfaces of scaffold. Fibroblasts maintain high proliferative ability and viability during long term cultivation. Spidroin 1-based scaffold are the perspective materials for bioengineering.